2007
DOI: 10.1111/j.1468-2427.2007.00754.x
|View full text |Cite
|
Sign up to set email alerts
|

The Return of the Slum: Does Language Matter?

Abstract: The 'cities without slums' initiative has resuscitated an old and dangerous term from the habitat vocabulary. Use of the word 'slum' will recreate many of the myths about poor people that years of careful research have discredited. The UN has employed the word in order to publicize the seriousness of urban problems and to improve its ability to attract funding with which to tackle the issue. But in using such an emotive word the UN risks opening a Pandora's box. The campaign implies that cities can actually ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
203
0
15

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(220 citation statements)
references
References 26 publications
2
203
0
15
Order By: Relevance
“…28 Para críticas eficaces de la retórica urbana de "ciudades creativas", "barrios marginales", "villas" y "renacimiento", "patrimonio" y "diversidad", y (anti) gueto, y etiquetas parecidas para distritos desposeídos y menospreciados, ver respectivamente Peck (2005), Gilbert (2007), Barnes et al (2006), Modan (2007) y Boyd (2008, y Wacquant, Slater y Pereira (2014).…”
Section: Aplicaciones: Numerosos Caminos En La Ciudad Bourdianaunclassified
“…28 Para críticas eficaces de la retórica urbana de "ciudades creativas", "barrios marginales", "villas" y "renacimiento", "patrimonio" y "diversidad", y (anti) gueto, y etiquetas parecidas para distritos desposeídos y menospreciados, ver respectivamente Peck (2005), Gilbert (2007), Barnes et al (2006), Modan (2007) y Boyd (2008, y Wacquant, Slater y Pereira (2014).…”
Section: Aplicaciones: Numerosos Caminos En La Ciudad Bourdianaunclassified
“…United Nations Human Settlements Programme, v nadaljevanju: UN-HABITAT) o izboljšanju stanovanjskih razmer v Gani potrjuje, da gre pri stanovanjih neustrezne kakovosti za tista v slumih, saj je bilo v njem med drugim zapisano, da »[č]eprav je stanovanje osnovna življenjska potreba, več kot polovica prebivalstva Gane živi v ,skromnih hišah, v katerih ni dostopa do ustreznih sanitarij, vode in ogrevanja, ki bi zadostili njihovim dnevnim fizičnim potrebam'« (UN-HABITAT, 2010: 4). Podobno kot v mnogih drugih državah po svetu (Gilbert, 2007) se ta razlaga običajno uporablja kot uradni vzrok za prisilno izselitev ali razselitev ljudi, ki živijo v teh neustreznih bivališčih. Tako kot prejšnje vlade je tudi zdajšnja ganska vlada že izvršila številne prisilne izselitve (ganski urbanistični inštitut, 2010).…”
Section: Uvodunclassified
“…Thus, according to him, to argue that land registration is the panacea to the problem of poverty and under development is to prescribe a simple solution to a complex problem, a solution which is insufficient and is not working. Other studies that have concluded that land registration per se cannot unlock capital include Domeher and Abdulai (2012), Abdulai (2010), Abdulai and Hammond (2010), Bromley (2008) and Gilbert (2007). In developing countries, a very critical determinant of economic development is prudent management of a nation's resources and good governance; deficiencies in these have been identified by Abdulai (2011) to be among the major causes of poverty and economic underdevelopment in, particular, Africa.…”
Section: Migotmentioning
confidence: 99%